Medication Adherence in Non-communicable Disease Management and the Impact of Health Literacy (Turkey Health Literacy Journal, 2021)
Noncommunicable diseases (NCDs) are the leading cause of death at the global, regional and national levels. NCDs kill 40 million people each year, equivalent to 70% of all deaths globally. Each year, 15 million people aged 30–69 years die from an NCD; over 80% of these premature deaths ocur in low- and middle-income countries. NCDs has been declared one of the major public health emergencies by the World Health Organization (WHO). Tackling with NCDs is a long and challenging process. Identification of NCDs risk factors, and early treatment is posiible through cheap and cost effective methods, but it is very important and necessary for patients to participate actively and consciously in this process. According to the Turkish Ministry of Health Report around 22 million people has NCDs all over the Turkey. Many studies have been carried out on the effect of Health Literacy on patients’ understanding of their diagnosis and planned treatment. In addition, it has been reported in the literature that the medicine adherence is one of the most important issue in the treatment and one the most problematic process as well. In this study, literature information on the effect of drug adherence and Health Literacy of patients in NCDs treatment is under review.